The influence mechanism of parental emotional companionship on children’s second language acquisition - Cheng, Xiaoxia; Zhou, Shike (Frontiers in Psychology, 2023)
It has become a consensus that parental emotional companionship can promote the healthy growth of children. However, the theoretical circle still knows little about the relationship between parental emotional companionship and children’s second language acquisition and the internal processes. In this study, the path analysis method was adopted to analyze the academic quality testing data of Grade 5 and Grade 9 students obtained by questionnaire survey method in Jiangsu Province in 2020, so as to explore the influence mechanism of parental emotional companionship on children’s second language acquisition. The results show that parental emotional companionship promotes second language acquisition. Learning confidence and internal learning motivation play an intermediary role in this relationship. Learning confidence positively influences internal learning motivation and plays a chain mediating role. The indirect effect of internal learning motivation in the middle school group is the masking effect. The conclusion of this study reveals the influence mechanism of parental emotional companionship on children’s second language acquisition, which enriches and deepens the theoretical understanding of the affective factors affecting second language acquisition. Theoretical and practical implications, along with limitations and future research directions were discussed.